Implementation of Multiplication Boards to Improve Students' Understanding of Multiplication 1-10 in Grade 3 of SDN Sembilangan - Irsyadah Yusuf; Nadia Elfa Riska; Azkia Najwa Rosyadi; Najwa Rahma Auliya; Agung Setyawan (Examinations: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study aims to determine the effectiveness of using a multiplication board in improving students' conceptual understanding and learning outcomes in multiplication 1-10 in grade 3 of Sembilangan Elementary School. Specifically, this study aims to describe the application of the multiplication board in mathematics learning and to determine the improvement in students' understanding after using this board. This research was motivated by students' low understanding of multiplication concepts due to previous learning methods still using memorization and lectures, which tended to make it difficult for students to grasp the concepts concretely. This study used a quantitative approach with a one-group pre-test and post-test design. The study was conducted in grade 3 of Sembilangan Elementary School, Bangkalan Regency, from February to March 2026. The subjects were 32 grade 3 students. Data sources were obtained from teachers and students, while data collection techniques were conducted through interviews, tests, observations, and documentation. The research instruments consisted of interview sheets, observation sheets, documentation, and written tests in the form of student worksheets (LKPD) for the pre-test and post-test. The instrument validity was measured using content validity tailored to the learning objectives and multiplication material for 1–10. Reliability was assessed through the consistency of pre- and post-test results. Data analysis used descriptive and inferential statistics using SPSS Statistics 23 using a paired sample t-test with a significance level of 0.05. The results showed a significant improvement in student learning outcomes after using the multiplication board. The average student score increased from 53.13 in the pre-test to 84.06 in the post-test. The statistical test results showed a calculated t-value of -20.443, which was greater than the t-table of 2.064. Therefore, the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. Therefore, it can be concluded that the use of the multiplication board was effective in improving the understanding of multiplication concepts among third-grade students at Sembilangan Elementary School. Teachers are advised to use concrete and engaging learning media to increase student engagement, enthusiasm, and ease in understanding mathematics, particularly multiplication.